Crescimento econômico e degradação ambiental no Pará à luz da Curva de Kuznets Ambiental entre os anos 2002 a 2018 - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2022)
The increase in environmental degradation caused by economic growth has become the focus of many debates in recent history. In 1991, the economists Grossman and Krueger proposed that the relationship between these two variables would generate, by itself, an improvement to the environment, causing an inverted "U" shaped curve, known as the Environmental Kuznets Curve (EKC). In this context, the general objective of this study was to analyze whether there is a relationship in the format proposed by the authors between economic growth and environmental degradation for the state of Pará between the years 2002 and 2018. To achieve this objective, two models were developed using the panel data technique, employing Ordinary Least Squares estimations for the fixed effects model in both cases. Model 1 used CO 2 emission as the dependent variable and model 2 used deforestation, and, in both models, the GDP per capita was the independent variable. It is noteworthy that the EKC hypothesis in its quadratic ("U" or inverted "U") and cubic ("N" or inverted "N") formats were tested. The results found in the first model rule out the possibility of the relationship between CO2 emission and GDP per capita being cubic between the years 2002 and 2018 in the state of Pará, indicating the existence of a quadratic curve with the concavity turned upward. In other words, although a reduction in CO2 emissions was initially observed, it would grow again after the curve reached its minimum point, in this case equal to R$ 15.531,70. In the second model, the cubic format was not significant either, showing, for the deforestation and GDP per capita relationship, a EKC as in the original proposal, in the form of an inverted "U". Thus, although at the beginning there was an increase in deforestation caused by the growth in income, when the maximum point of the curve was reached, equal to R$ 12.415,44, this same movement of economic growth would be providing a reduction in the process of deforestation in the time frame adopted in the study. In this sense, the results do not give us evidence to infer about the existence of the EKC, at least not in its original format, for the state of Pará between the years 2002 and 2018.
Keywords: Curva de Kuznets Ambiental; Crescimento econômico; Degradação Ambiental; Emissão de CO²; Desmatamento; CNPQ::CIÊNCIAS HUMANAS